Effect of high-intensity perturbations during core-specific sensorimotor exercises on trunk muscle activation. (21st March 2018) - Mueller, Juliane; Hadzic, Miralem; Mugele, Hendrik; Stoll, Josefine; Mueller, Steffen; Mayer, Frank
Abstract: Core-specific sensorimotor exercises are proven to enhance neuromuscular activity of the trunk. However, the influence of high-intensity perturbations on training efficiency is unclear within this context. Sixteen participants (29 ± 2 yrs; 175 ± 8 cm; 69 ± 13 kg) were prepared with a 12-lead bilateral trunk EMG. Warm-up on a dynamometer was followed by maximum voluntary isometric trunk (flex/ext) contraction (MVC). Next, participants performed four conditions for a one-legged stance with hip abduction on a stable surface (HA) repeated randomly on an unstable surface (HAP), on a stable surface with perturbation (HA + P), and on an unstable surface with perturbation (HAP + P). Afterwards, bird dog (BD) was performed under the same conditions (BD, BDP, BD + P, BDP + P). A foam pad under the foot (HA) or the knee (BD) was used as an unstable surface. Exercises were conducted on a moveable platform. Perturbations (ACC 50 m/sec 2 ;100 ms duration;10rep.) were randomly applied in the anterior-posterior direction. The root mean square (RMS) normalized to MVC (%) was calculated (whole movement cycle). Muscles were grouped into ventral right and left (VR;VL), and dorsal right and left (DR;DL). Ventral-Dorsal and right-left ratios were calculated (two way repeated-measures ANOVA;α = 0.05). Amplitudes of all muscle groups in bird dog were higher compared to hip abduction (p ≤ 0.0001; Range: BD: 14 ± 3% (BD;VR) to 53 ± 4%; HA: 7 ± 2% (HA;VR) to 16 ± 4% (HA;DR)). EMG-RMS showed significant differences (p < 0.001) between conditions and muscle groups per exercise. Interaction effects were only significant for HA (p = 0.02). No significant differences were present in EMG ratios (p > 0.05). Additional high-intensity perturbations during core-specific sensorimotor exercises lead to increased neuromuscular activity and therefore higher exercise intensities. However, the beneficial effects on trunk function remain unclear. Nevertheless, BD is more suitable to address trunk muscles.